PENGARUH TECHNOLOGY ENHANCED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD INPRES PARANGLABBUA KEC. PARIGI, KAB. GOWA - Hasnini; Ernawati; Ardhila Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to determine the effect of Technology Enhanced Learning onstudent learning outcomes in mathematics subjects for grade V of SD Inpres Paranglabbua,Parigi District, Gowa Regency. This study is a quantitative study with a one group pretest-posttest design. The subjects of the study were 15 grade V students. Data collectiontechniques used were observation, testing, and documentation. Data analysis techniques inthis study were descriptive data analysis techniques and T-Test tests. The results showed thatthere was an effect of the use of Technology Enhanced Learning on student learningoutcomes in mathematics subjects for grade V of SD Inpres Paranglabbua. This is indicatedby the average pretest score reaching 52, while the average posttest score reached 76. Basedon the results of the t-test analysis on the effect of Technology Enhanced Learning on studentlearning outcomes in mathematics subjects, it shows that the results of the hypothesis testobtained t_count = 7.18 and t_table = 2.145 so that t_(count) > t_table or 7.18 > 2.145 in otherwords H_0 is rejected and H_1 is accepted, which means that there is an effect of TechnologyEnhanced Learning on student learning outcomes in mathematics subjects in grade V of SDInpres Paranglabbua Kec. Parigi, Kab. Gowa.